2013
DOI: 10.1007/s00590-013-1176-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioabsorbable sutures versus screw fixation of displaced tibial eminence fractures: a biomechanical study

Abstract: Fixation with strong trans-osseous sutures is stronger than fixation with a cannulated screw and washer on cadaveric knees. It appears that fixation with strong trans-osseous sutures allows immediate mobilisation and weight bearing like fixation with a cannulated screw and washer. Meanwhile, the time for fixation with trans-osseous sutures is significantly longer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…18,62 Despite assumptions regarding the superior rigidity of metal implants, multiple biomechanical studies suggest that suture techniques actually result in stronger and more durable reduction of tibial spine fractures under cyclic loading simulating physiologic knee function. [87][88][89][90] Furthermore, the systematic review by Bogunovic et al found that patients treated with screws had a higher prevalence of clinical instability with Lachman and KT arthrometer testing (27% vs. 13%, p ¼ 0.0069) as well as higher rates of hardware removal (65% vs. 4%, p < 0.005) compared with suture fixation. However, there was no difference in patient-reported instability.…”
Section: Fixation Techniquesmentioning
confidence: 99%
“…18,62 Despite assumptions regarding the superior rigidity of metal implants, multiple biomechanical studies suggest that suture techniques actually result in stronger and more durable reduction of tibial spine fractures under cyclic loading simulating physiologic knee function. [87][88][89][90] Furthermore, the systematic review by Bogunovic et al found that patients treated with screws had a higher prevalence of clinical instability with Lachman and KT arthrometer testing (27% vs. 13%, p ¼ 0.0069) as well as higher rates of hardware removal (65% vs. 4%, p < 0.005) compared with suture fixation. However, there was no difference in patient-reported instability.…”
Section: Fixation Techniquesmentioning
confidence: 99%
“…In addition, the fixation device should not traverse the proximal tibial growth plate in skeletally immature patients because of the possibility of partial physeal arrest [ 17 , 18 ]. Some biomechanical studies have investigated fixation power of several internal fixation devices with different results [ 19 24 ]. Some clinical studies have reported outcomes of various fixation devices and surgical techniques with pros and cons [ 9 , 10 , 25 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the arthroscopic methods are most commonly applied to stabilize the displaced bony fragment of the tibial eminence nowadays. 28 Much has been published about the different techniques for arthroscopic-assisted reduction and internal fixation for tibial eminence fractures, including absorbable surgical suture of the fragment, fixation with a wire knot, fixation with a cannulated screw, fixation with K-wire, stabilization using absorbable elements, and so on. However, two modes of fixation, suture and screw drilled through bone tunnels are most commonly described, with both satisfactory postsurgery outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the arthroscopic methods are most commonly applied to stabilize the displaced bony fragment of the tibial eminence nowadays. 28…”
Section: Discussionmentioning
confidence: 99%